Reproductive biology of the Brazilian guitarfish, Pseudobatos horkelii (Muller & Henle, 1841) from southeastern Brazil, western South Atlantic - Martins, M. F. [UNESP]; Pasquino, A. F. [UNESP]; Gadig, O. B. F. [UNESP] (Wiley-Blackwell, 2018)
This study provides information on the seasonal occurrence, length-width relationship, sexual development and size at first maturity of the critically endangered Brazilian guitarfish Pseudobatos horkelii in southeastern Brazil. Samples were obtained from September 2007 to August 2009 from commercial fisheries off Sao Paulo State coast at depths of 10-50 m, with net mesh sizes of 150 mm in the main net and 100 mm in the cod end. A total of 143 specimens (71 males, 72 females) were analyzed. Total length (TL), disc width (DW), sex and reproductive variables were recorded for each individual. Pseudobatos horkelii presents sexual dimorphism in length-width relationships, with females attaining larger TL and DW. Females also mature at a larger TL, at 81.1% of the maximum TL, while males mature at 67.8% of the maximum TL. No specimens were captured in winter, and only a small sample size was observed in autumn. Males captured in spring and summer presented semen in the seminal vesicle, indicating that this species may reproduce in the warmer months, as already observed for other Rhinobatidae as well as for P. horkelii in southern Brazil.